PEMAHAMAN GURU BAHASA INDONESIA SMP DAN MTS DI KOTA BIMA TERHADAP PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS - Lestari, Fujiah; Mahsun, Mahsun; Burhanudin, Burhanudin (Universitas Hamzanwadi, 2022)
This study aims to obtain information about the understanding of junior high school teachers and MTs in the city of Bima towards learning text-based Indonesian. This type of research is a descriptive study using qualitative and quantitative approaches. The targets in this study are Indonesian of junior high school and MTs language teachers in the city of Bima. The method used in the process of collecting data in this research is the listening method and proficient method. While the method used in data analysis is the intralingual equivalent method of HBB, HBS, and HBSP techniques. Based on the analysis results obtained that the understanding of Indonesian of junior high school and MTs in the city of Mataram towards learning Indonesian based on text categorized less fortunate. The understanding of junior high school teachers and MTs Indonesian language teachers in Bima on text-based Indonesian language learning is able to understand the types of texts based on their genre, because all respondents are able to describe their understanding in the text itself. From the point of view of the understanding of Indonesian of junior high school and MTs language teachers in the city of Bima on learning text-based Indonesian language is able to understand the structure of the text based on its genre, because all respondents were able to describe their understanding in the text based on the genre. The understanding of junior high school and MTs Indonesian language teachers in Bima on learning text-based Indonesian is less able to understand the use of linguistic tools in the text, because most respondents are less able to describe their understanding in text based on their genre. And finally, the understanding of junior high school and MTs Indonesian language teachers in Bima on learning text-based Indonesian in Bima City is able to understand the social objectives in the text, because all respondents are able to describe their understanding in text based on their genre.Keywords: Teacher Understanding, Indonesian Language Learning, Text.